PENGARUH PERMAINAN PETAK UMPET TERHADAP KEMAMPUAN INTERPERSONAL ANAK PADA ANAK USIA 4-5 TAHUN DI TK ISLAM AS-SALAM BEKASI - Tadya Syiffa; Roza Yenita, Rita Intan Anggraeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the traditional game of hide-and-seek on the interpersonal skills of early childhood. Hide-and-seek, as a form of cooperative play, is believed to stimulate children's social skills, such as the ability to interact, cooperate, and understand others' feelings. The research method used was a quantitative approach with a correlation design. The subjects were 10 children aged 4-5 at As-Salam Islamic Kindergarten, Bekasi. Data were collected through observation using a child interpersonal skills instrument. The results showed that children who actively participated in hide-and-seek experienced significant improvements in communication, empathy, and cooperation compared to before the treatment.